The Bolds on Holiday - Clary, Julian; David Roberts Ill. (London Andersen Press Limited, 2017)
It's the summer holidays, and the hairiest family in Teddington decide to take a well-earned holiday by the seaside. With their extended hyena family in tow, they head on down to Cornwall for a spot of camping. But it's never long before trouble sniffs these hyenas out, and Bobby is mistaken for a pup and snatched by a wicked dognapper.